Optimization of strontium removal by tetraselmis chui grown in bubble column photobioreactors - Segovia-Campos, Inés (2024)
Green microalgae of the class Chlorodendrophyceae have recently attracted the interest of researchers due to their ability to form micropearls (intracellular inclusions of amorphous calcium carbonate) highly enriched in Sr. The marine species Tetraselmis chui (included in the class Chlorodendrophyceae) shows high uptake of both stable and radioactive Sr isotopes and has been suggested as a potential candidate for the development of new bioremediation tools regarding radioactive Sr-90 pollution. In this study, we optimized Sr removal from seawater by growing T. chui in 1-L bubble column photobioreactors (PBRs) with and without CO2 supply. Culturing T. chui in bubble column PBRs greatly improves cell production and Sr removal compared to previous studies. Furthermore, the addition of 10 mL L-1 h(-1) CO2 further accelerates T. chui growth and results in better Sr removal rates. This study presents promising results for the development of new bioremediation methods to treat Sr-90 pollution.